2021
DOI: 10.3389/fonc.2021.738177
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Cholesterol Metabolism in Ovarian Cancer: Identification of Novel Therapeutic Targets

Abstract: Cholesterol is an essential substance in mammalian cells, and cholesterol metabolism plays crucial roles in multiple biological functions. Dysregulated cholesterol metabolism is a metabolic hallmark in several cancers, beyond the Warburg effect. Reprogrammed cholesterol metabolism has been reported to enhance tumorigenesis, metastasis and chemoresistance in multiple cancer types, including ovarian cancer. Ovarian cancer is one of the most aggressive malignancies worldwide. Alterations in metabolic pathways are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 120 publications
(172 reference statements)
0
22
0
Order By: Relevance
“…Pyroptosis-restricting metabolic changes are necessary for cancer cell survival. 209 Li et al 210 found that IL-1α and IL-1β were overexpressed in a 1992 investigation on epithelial tumor cell lines and tumor cells derived from the ascitic fluid of ovarian cancer patients. In ovarian cancer cells with the 185delAG founder mutation in the breast cancer susceptibility gene 1, there was an increase in active IL-1 and elevation in caspase 1 cleavage mediated by inflammasome.…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis-restricting metabolic changes are necessary for cancer cell survival. 209 Li et al 210 found that IL-1α and IL-1β were overexpressed in a 1992 investigation on epithelial tumor cell lines and tumor cells derived from the ascitic fluid of ovarian cancer patients. In ovarian cancer cells with the 185delAG founder mutation in the breast cancer susceptibility gene 1, there was an increase in active IL-1 and elevation in caspase 1 cleavage mediated by inflammasome.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…This imbalance is usual in cancers, particularly ovarian cancer. Pyroptosis‐restricting metabolic changes are necessary for cancer cell survival 209 . Li et al 210 .…”
Section: Pyroptosis and Inflammasomes In Cancermentioning
confidence: 99%
“…Low-grade plasmacytomas, endometrioid carcinomas, clear cell carcinomas, and mucinous carcinomas are examples of type I tumors. High-grade plasmacytomas and undifferentiated carcinomas are examples of type II tumors ( He et al, 2021 ). High-grade plasmacytomas and undifferentiated carcinomas are the two main type II tumors.…”
Section: Structure and Function Of Npc1l1mentioning
confidence: 99%
“…Given that this imbalance is common in cancers (82), including ovarian cancer, the hypothesis is that there is a greater difficulty in pore formation, because of the higher levels of phosphatidylinositide and cholesterol in cell membrane, which makes the cancer cells viable (83). Cholesterol metabolism is altered in ovarian cancer (84). Thus, pyroptosis, impaired by metabolic alterations, plays a crucial role in the overall survival of ovarian cancer cells.…”
Section: Gsdmmentioning
confidence: 99%